SEFT® Therapy (Spiritual Emotional Freedom Technique) To Reduce The Tendency To Smoking In Early Adolescents - Lely Ika Mariyati; Nur Habibah (Psikologia : Jurnal Psikologi, 2013)
SEFT® therapy was given to maximize the effectivity of the body energy system which used the EFT technique (tapping) with spiritual power (pray and surrender). The aim was stabling mind and feeling in order to positivy the self concept and the self control of early adolescent. This research was quantitative experimental approach with pretest-posttest one group design. The variable was SEFT® therapy as the independ ent variable and the smoking prefference as the dependent variable. The sampling technique was cluster random sampling gotten two Yunior High School in Waru region and random assignment gotten twelve students as experimental group research. The instruments data collection was the prefference smoking scale. The data was, analyzed by Wilcoxon Mathch Pairs Test,with SPSS 16 program, gotten ( p = 0,004; p<0,01), it was meant that there was the differences between the smoking prefference on early adolescents before and after given SEFT® therapy. The difference of smoking prefference was seen from the average posttest was lower than pretest (49 < 60), the result of follow up average was lower than the posttest (41 < 49). The result of the research showed that SEFT® therapy able to decerase the smoking prefference of early adolescents.